1992
DOI: 10.1111/j.1365-2621.1992.tb14327.x
|View full text |Cite
|
Sign up to set email alerts
|

Red Beet Pigment Composition. Effects of Fermentation by Different Strains of Saccharomyces cerevisiae

Abstract: Determination of pigmentsPasteurized red beet juice was inoculated with seven strains of Saccharomyces cerevisiue after adjusting pH to 5.8. Fermentation was at 26°C. The decay of red beet pigments was spectra-photometrically determined and expressed as betanine. Average percentages of betanine, isobetanine, betanidine, isobetanidine and the saccharide components were monitored by HPLC. After 40 hr fermentation, the strains Oenoferm, 1090 and Tokaj 76D showed pigment retentions and sucrose concentrations (g.L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…These processes are more efficient on recovering betalains from beet tissue when compared to conventional hydraulic techniques (Real & Cerezal, 1995). Since approximately 80% of beet juice solids consist of fermentable carbohydrates and nitrogenous compounds, fermentation processes have been applied to remove these materials (Drdák et al. , 1992), thus increasing betalain concentrations.…”
Section: Betalain Extractionmentioning
confidence: 99%
“…These processes are more efficient on recovering betalains from beet tissue when compared to conventional hydraulic techniques (Real & Cerezal, 1995). Since approximately 80% of beet juice solids consist of fermentable carbohydrates and nitrogenous compounds, fermentation processes have been applied to remove these materials (Drdák et al. , 1992), thus increasing betalain concentrations.…”
Section: Betalain Extractionmentioning
confidence: 99%
“…; Drdak et al . ). The presence of these metabolites in beetroot produces an earthy like flavor, which limits its application in dairy products (Lu et al .…”
Section: Introductionmentioning
confidence: 97%
“…Lower contents of anthocyanins were observed in the skins of grape berries of the varieties Blauer Portugieser and Pinot noir (25.3 and 20.7 mg/g of dry skin, respectively) (Table 2, Figure 1). Drdák et al (1991) compared the total contents of anthocyanins in the dry skins of blue grape varieties (Vitis vinifera L.) and of interspecific hybrids and recorded contents ranging from 12.8 to 105.0 mg/g of dry skin. Out of all varieties of Vitis vinifera L. under the study, they found the highest concentration of pigments in the grapes of the variety Neronet (78.4 mg/g dry skin).…”
Section: Resultsmentioning
confidence: 99%
“…Anthocyanins were extracted from the grapes using a modified method described by Drdák et al (1991). From each grape, altogether 10-15 g of berries were extracted by discontinuous homogenisation in a mixer containing 100 ml of acidified methanol (0.1% HCl in methanol).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation